2013
DOI: 10.5152/dir.2013.12132
|View full text |Cite
|
Sign up to set email alerts
|

The role of apparent diffusion coefficient values in the differential diagnosis of breast lesions in diffusion-weighted MRI

Abstract: ORIGINAL ARTICLE PURPOSE We aimed to determine the apparent diffusion coefficients (ADCs) of focal breast lesions on diffusion-weighted magnetic resonance imaging (DW-MRI) and to evaluate whether ADC measurement can be used to characterize lesions as benign or malignant. MATERIALS AND METHODSFifty-one patients between the ages of 18-79 years (mean age, 48.5 years) with 51 histopathologically verified breast lesions were included in this study. The patients were examined with a 1.5 Tesla system using a bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…When we determined a threshold value as 0.9, the sensitivity went up 96% and the specificity was 89%. Similar studies in the literature reported that measuring the ratio of ADC values for healthy breast tissues and lesions helped diagnostic accuracy, whereas an increase in sensitivity caused a decrease in specificity in our study (23,29).…”
Section: Discussionsupporting
confidence: 67%
“…When we determined a threshold value as 0.9, the sensitivity went up 96% and the specificity was 89%. Similar studies in the literature reported that measuring the ratio of ADC values for healthy breast tissues and lesions helped diagnostic accuracy, whereas an increase in sensitivity caused a decrease in specificity in our study (23,29).…”
Section: Discussionsupporting
confidence: 67%
“…20,33 In our series, the patients of carcinoma did not have excessive areas of necrosis, explaining the inability to differentiate between carcinoma and lymphoma by ADC values. 42 In our study, the lowest ADC value in the malignant group was seen with undifferentiated carcinoma. 41 Addition of DW-MRI and ADC mapping during routine MRI examination can be done without the need of extra time or contrast injection.…”
Section: Discussionsupporting
confidence: 43%
“…Some groups raised the sensitivity (93-96%) of the ADC, reducing specificity (55-56%). 19,24 Others aimed the opposite, reducing sensitivity (52-70%) with high specificity (85-100%), 2,25,26 or optimized sensitivity and specificity simultaneously (86-92%). 27,28 Recently, meta-analysis of DWI for detecting breast pathology showed a sensitivity between 84 and 91% and specificity between 75 and 84%.…”
Section: Discussionmentioning
confidence: 99%